A case report of a child with severe burns treated using a multimodal approach - Liu, Xiaoyu; Huang, Guobao (Frontiers in Pediatrics, 2025)
IntroductionBurns are a common injury in children, with severe burns carrying high disability and mortality rates.MethodsThis case report summarizes the treatment, in our department, of a 9-year-old child with burn injuries caused by flame exposure, involving a total burn area of 50%, with depth ranging from third to fourth degree, and associated with mild shock.ResultsFollowing active fluid resuscitation and anti-shock treatment, the child underwent staged wound excision and debridement, autologous and allogeneic skin grafting, and artificial dermal scaffold implantation. All wounds were successfully closed, with healing achieved within 77 days.DiscussionInsights from this case report may be applied to improve therapeutic outcomes for children with severe burns.